Board and audit committee effectiveness, ethnic diversification and earnings management: a study of the Malaysian manufacturing sector. Issue 4 (1st August 2016) - Wan Mohammad, Wan Masliza; Wasiuzzaman, Shaista; Nik Salleh, Nik Mohamad Zaki
Abstract : Purpose: This study examines the implications of the Revised Malaysian Code on Corporate Governance (2007) towards the effectiveness of the board and audit committees in Malaysian manufacturing companies. Since the manufacturing firms are dominantly held by Chinese firms, this paper is extended to incorporate the implication of ethnicity on board and audit committees' effectiveness. Design/methodology/approach: Using a sample of 201 firms from fiscal year 2004-2009, the dataset consists of a total of 1206 firm-year observations. Analysis is carried out using correlation analysis, multiple and logistic regression analyses. Findings: The findings reveal that board and audit committees' effectiveness is positively associated with earnings management pre- and post-Revised Malaysian Code on Corporate Governance (2007). A higher number of ethnic members in the board are also positively associated with earnings management. Research limitations/implications: This study is limited to some industries in the manufacturing sector due to the special characteristics of this sector and covers mostly large firms. The results may not therefore be applicable to small firms. Finally, the study does not consider possible interaction between the board and audit characteristics which may be significant in influencing earnings management. Practical implications: The findings show that the corporate governance mechanism in Malaysian firms is currently inadequate in preventing earnings management and extra effort is needed to improve board governance. Originality/value: This paper contributes to the current literature on the issues of corporate governance effectiveness and board ethnicity in the current economic and political structure in Malaysia.